A Field Study on Evaluating Mental Workload in “Kerupuk Emping” Small and Medium-Sized Enterprise in Hanau Berak Village, Lampung - Muhammad Attar; Indah Puspita Sari; Suryaneta (Indonesian Journal of Economic & Management Sciences, 2023)
This study examined the mental workload of employees in small and medium-sized enterprises (SMEs) engaged in the production of “Kerupuk Emping” in Hanau Berak Village, Lampung. Using both qualitative and quantitative techniques for data collection, a mixed-methods strategy was employed. The NASA-TLX questionnaire was utilized to measure mental burden, including mental demand, physical demand, temporal demand, performance, effort, and frustration. In addition, semi-structured interviews were used to acquire a deeper understanding of the experiences of the participants. The findings revealed that employees of “Kerupuk Emping” small and medium-sized enterprises experienced a substantial mental burden. This study’s findings can inform interventions aimed at reducing mental burden in the workplace, resulting in improved employee health and well-being and increased SME productivity